Morphological Characteristics and Lung Function of the Pilots of Montenegro Army - Boris Banjevic; Boris Zarkovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2022)
The results of numerous medical studies and kinesiology research show the existence of differences in the lung function with reference to age, body height and the ratio of certain parameters of body composition. The aim of this research is to determine the status of morphological characteristics and the lung function with the pilots of Montenegro Army. The sample of examinees consisted of 30 military pilots of the age 36.3±11. The sample of measures was made of 4 indicators for the assessment of longitudinal dimension, transverse dimension, body mass and volume, subcutaneous fat, body composition and lung function. Central and dispersion variables parameters were calculated. The specificities of the body height of pilots as well as the excessiveness in their body weight were calculated, while the parameters of lung volumes and capacities and the parameters of the flow of respiratory passageways have shown the satisfactory condition of their respiratory function. In addition, it was shown that the pilots are soldiers without individual medical risks in the sense of obesity appearance or obstructive ventilation disturbances. The obtained results indicate the need to conduct research in which the effect of certain morphological measures and parameters of the pilot's body composition to their lung function would be dominantly studied. In that way we would obtain significant data both for the military organisation in the sense of promoting the training system and realization of target tasks, and for the kinesiology science from the aspect of determining certain regularities of the functioning of human body in specific life and work conditions in the army.